The Baby Hatch at the Crossroads of Human Rights - Novak, Stjepan; Novak, Antonija (Review of European and Comparative Law, 2026)
When the baby hatch (known as “Window of Life”) came under public scrutiny in the Republic of Croatia, it was met with a number of criticisms. The most prominent among them were its lack of regulation under Croatian law, the alleged encouragement of committing a criminal offense, and the violation of the child’s right to identity. Neither the concept of the baby hatch, nor the criticisms directed at this method of caring for unwanted newborns are new in Europe or beyond, nor are they unfamiliar to the case law of the European Court of Human Rights. This paper will attempt to demonstrate that the only well-founded objection is the lack of adequate legal regulation. The claim that the existence of the baby hatch encourages criminal behavior is simply unfounded, while the potential violation of the child’s right to know their identity can be justified by the protection of a higher right – the right to life.